Unfolding Indian Elections (New Delhi, 2017)
India has able to uphold its democracy, through the ebb and flow of political and security challenges. India has proved its detractors wrong, and survived the crises that befell on many Asian and African nations in post-colonial era. A large measure of credit should go to India?s free and fair elections. They have reflected the people?s will, and provided for seamless transition of power at the Centre and the states. Their results have seldom been challenged, and accepted by the electorate and people?s representatives This is something we should be proud of in the world's largest democracy
Keywords: Political Science